2008
DOI: 10.1111/j.1365-2788.2008.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and nature of intellectual disability in Norwegian prisons

Abstract: The prevalence of ID in Norwegian inmates is significant, measured by WASI and HASI. Identification, rehabilitation and care, concerning an intellectual handicap, are mostly absent in the Norwegian criminal justice system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
90
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 25 publications
13
90
1
6
Order By: Relevance
“…This finding is congruent with results from previous studies (Ford et al, 2008;Sondenaa et al, 2007Sondenaa et al, , 2008Sondenaa et al, , 2011. The correlation of 0.69 in this study lies within the range of results of previous studies using the WAIS-III as a criterion of validity: Sondenaa et al (2007) found a correlation of 0.81 in a psychiatric setting, whereas Ford et al (2008) found a correlation of 0.55 in an adolescent offender sample.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This finding is congruent with results from previous studies (Ford et al, 2008;Sondenaa et al, 2007Sondenaa et al, , 2008Sondenaa et al, , 2011. The correlation of 0.69 in this study lies within the range of results of previous studies using the WAIS-III as a criterion of validity: Sondenaa et al (2007) found a correlation of 0.81 in a psychiatric setting, whereas Ford et al (2008) found a correlation of 0.55 in an adolescent offender sample.…”
Section: Discussionsupporting
confidence: 91%
“…The assessment results in an index that had been found to correlate significantly with those on the Kaufman Brief Intelligence Test and on the Vineland Adaptive Behavior Scales (Hayes, 2002). The HASI also correlated significantly with the WASI (Sondenaa et al, 2008(Sondenaa et al, , 2011 and the WAIS-III (Ford et al, 2008;Sondenaa et al, 2007). Using the original HASI cut-off score of 85 (Hayes, 2002), previous research using a Receiver Operating Characteristic (ROC) curve analysis have reported a sensitivity of 100% using the WAIS-III (Sondenaa et al, 2007) or WASI (Sondenaa et al, 2011) as a criterion validity and a specificity of 35.4% when using the WASI (Sondenaa et al, 2011), and 57% when using the WAIS-III (Sondenaa et al, 2007) …”
Section: Procedures and Instrumentsmentioning
confidence: 95%
See 2 more Smart Citations
“…The present authors have conducted research on ID in a prison population, where both types of problems are significant, and where quality of care is impacted [12]. When presented with the instrument and evidence above, we approached the originators of the PDCC and received permission to do a Norwegian translation.…”
Section: Introductionmentioning
confidence: 99%